Description of a new species of the Neotropical cichlid genus Gymnogeophagus Miranda Ribeiro, 1918 (Teleostei: Cichliformes) from the Middle Paraná basin, Misiones, Argentina - Alonso, Felipe (2019)
Gymnogeophagus jaryi, new species, is described from Southern tributaries of the Middle Paraná basin in Misiones. It can be distinguished from all other members of the genus, except from G. australis and G. caaguazuensis, by the presence of a hyaline to grey anterior portion of the dorsal fin. Gymnogeophagus jaryi differs from G. caaguazuensis by a longer caudal peduncle, caudal fin not lyrate, central portion of scales on dorsal portion of trunk light iridescent blue and by white spots in soft portion of dorsal fin in adult males, and from G. australis by the light iridescent blue coloration of central portion of scales on the dorsal portion of trunk and tail, and by the lack of scales on the soft portion of the dorsal fin. Additionally, it can be diagnosed by the following unique combination of characters: 10-11 dorsal-fin branched rays, 27-30 E1 scales, absence of lips thickening, and, in males, by the possession of a hump in adults, caudal fin not lyrate, presence of large white spots forming transversal stripes distally and in anterior area of the dorsal fin's soft portion, central area of scales on the dorsal portion of the trunk light iridescent blue, lack of scales on the base of the dorsal fin's soft portion, absence of a conspicuous and oblique dark band from the eye to the anterior border of the head, anterior portion of dorsal fin hyaline to grey, scales of the midlateral spot each bearing a semicircular light blue blotch, head hump starting at the horizontal through the eyes, concave anterior profile in lateral view, base of unpaired fins yellow, and whitish hyaline spots on caudal fin. The new species, based on mtDNA phylogeny, is the sister species of G. caaguazuensis from the Paraguay basin and is closely related to G. australis.